The great Gatsby - Fitzgerald, F. Scott (Francis Scott), 1896-1940. (New York : Scribner Paperback Fiction, 1995)
Jay Gatsby had once loved beautiful, spoiled Daisy Buchanan, then lost her to a rich boy. Now, mysteriously wealthy, he is ready to risk everything to woo her back. This is the definitive, textually accurate edition. The first edition contained a number of errors resulting from Fitzgerald's extensive revisions and a rushed production schedule.
Narrator Nick Carraway has recently moved to New York to work as a bond salesman; he meets his mysterious neighbor, the extravagantly wealthy Jay Gatsby. As Nick befriends Gatsby and learns of the lost love that motivates his behaviour, the novel explores the Roaring 20s, and that decade's cynical evocation of The American Dream.
Includes bibliographical references (p. [213]-214).
Keywords: Gatsby, Jay -- (Fictitious character) -- Fiction; Buchanan, Daisy -- (Fictitious character) -- Fiction; Man-woman relationships -- New York (State) -- Long Island -- Fiction; Upper class -- New York (State) -- Long Island -- Fiction; Traffic accidents -- Fiction; First loves -- Fiction; Rich people -- Fiction; Mistresses -- Fiction; Revenge -- Fiction; Long Island (N.Y.) -- Fiction; Love stories; Psychological fiction; Romance fiction; Novels